2022
DOI: 10.1002/ps.7008
|View full text |Cite
|
Sign up to set email alerts
|

A non‐chemical weed control strategy, introducing duckweed into the paddy field

Abstract: BACKGROUND Herbicide resistance in weeds and environmental pollution resulting from excessive application of chemical herbicides keeps increasing. Development of environment‐friendly and effective weed management strategies are required for sustainable agricultural production. In this study we investigated the effects of duckweeds (Landoltia punctata (G. Meyer) Les & D. J. Crawford and Spirodela polyrhiza (Linnaeus) Schle iden) introduction on the weed community and rice growth in paddy fields. RESULTS The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 51 publications
(124 reference statements)
3
13
0
Order By: Relevance
“…This indicates that the duckweed had adverse effects on the rice at the early-growth stage but had beneficial effects at the late-growth stage, even under the circumstance of growing in the fertile pond-bottom soil, which was rich in nutrients. This result agrees with those in a previous report by Wang et al [ 26 ], where the authors found trends in rice-tillering inhibition and spikelet enhancement caused by the duckweed coverage in a paddy field. The tillering inhibition was attributed to the nutrient competition between the duckweed and rice seedlings [ 14 ] or the suppression in the tiller-bud outgrowth induced by the duckweed shading [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This indicates that the duckweed had adverse effects on the rice at the early-growth stage but had beneficial effects at the late-growth stage, even under the circumstance of growing in the fertile pond-bottom soil, which was rich in nutrients. This result agrees with those in a previous report by Wang et al [ 26 ], where the authors found trends in rice-tillering inhibition and spikelet enhancement caused by the duckweed coverage in a paddy field. The tillering inhibition was attributed to the nutrient competition between the duckweed and rice seedlings [ 14 ] or the suppression in the tiller-bud outgrowth induced by the duckweed shading [ 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…This may have the same role as the N fertilizer applied at the panicle initiation practiced by farmers to increase the spikelet number and, thereby, increase the yield. In a recent report, a rice yield increase of 10.8–23.7% by duckweed coverage in a paddy field was attributed to the increase in the panicle size or grain number per panicle [ 26 ]. In addition, duckweed coverage in a paddy field prevented weed growth, especially in the early rice season [ 26 ], because the duckweed coverage blocked the sunlight and impeded the photosynthesis of weeds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weeds are native to many ecosystems and are characterized by the fact that they can typically survive under harsh conditions and compete with other plants for water, nutrients, and sunlight. The impact of weeds on crop yield is estimated to vary from 8% to 37% worldwide. The use of artificially synthesized chemical herbicides is currently the most economic and effective measure for weed growth management. However, over time, the weeds evolve to exhibit resistance to such herbicides, and the application of herbicides of different chemotypes has also become problematic as some weeds have evolved cross-resistance to multiple chemotypes herbicides. , …”
Section: Introductionmentioning
confidence: 99%